When Do Leaders Free‐Ride? Business Experience and Contributions to Collective Defense. Issue 2 (17th January 2020) - Fuhrmann, Matthew
Abstract: The logic of free‐riding expects that individuals will underinvest in public goods, but people often behave in ways that are inconsistent with this prediction. Why do we observe variation in free‐riding behavior? This study addresses this question by examining contributions to an important international public good—collective defense in military alliances. It develops a behavioral theory of free‐riding in which the beliefs of world leaders are important for explaining investments in public goods. The argument holds that leaders with business experience make smaller contributions to collective defense because they are egoistic and more comfortable relying on a powerful ally for their defense. An analysis of defense expenditures in 17 non‐U.S. members of the North Atlantic Treaty Organization from 1952 to 2014 provides evidence consistent with the theory. The findings suggest that leaders with business experience are more likely than other heads of government to act as self‐interested utility maximizers.